Pressure Comfort Evaluation for Supportive Waist Protections (Journal of Fiber Bioengineering and Informatics, 2024)
Supportive waist protection is the most used among various functional waist protection products. Itachieves its supportive effect primarily through elastic-banded supportive strips, with their shape,number, and material influencing the level of support. This study assesses the subjective and objectivepressure comfort of waist protection with different support strip designs, utilizing a combination ofsubjective pressure numerical representation and the Novel-appliance pressure testing system. Thefindings indicate that pressure from supportive waist protection is primarily concentrated in the posteriorand lateral lumbar regions, with the lateral region experiencing greater pressure than the anterior andposterior centre regions. Moreover, pressure along the abdominal circumference line generally exceedsthat along the waist circumference line. The comfortable pressure value in the posterior waist regionexceeds that in the lateral and frontal regions. Finally, varying shapes, numbers, and materials of supportstrips result in different pressure intensities in the posterior waist region, with 4 strips of bionic materialoffering the best waist comfort and 4 strips of steel plate providing the least comfort.
Keywords: Supportive Waist Protection; Support Strip Design; Pressure Comfort; Subjective and Objective Evaluation.